Ageing workforce : determinar e caracterizar os diferentes clusters de colaboradores para uma melhor compreensão da sua diversidade - Guerreiro, Ana Margarida Sabino (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence